Повишени нивои лептина код мајке могу бити показатељ субклиничког неонаталног хипотироидизма - KARPUZOGLU, HANDE (Journal of Medical Biochemistry, 2021)
Background: Several factors may influence newborn thyroid-stimulating hormone (TSH) concentrations and cause subclinical hypothyroidism in the newborn. A sufficient level of leptin signaling is needed for the normal production of TSH and the production of thyroid hormones by the thyroid gland. In our study, we aimed to investigate the correlation between maternal serum leptin concentration during the third trimester of pregnancy and newborn screening-TSH levels. Methods: This prospective cross-sectional study was conducted in clinics of obstetrics and gynecology of a state hospital between June and August 2013. Maternal venous blood samples were collected from 270 healthy pregnant women in the third trimester just before delivery. Measurement of maternal fT3, fT4, TSH, anti-thyroid peroxidase (TPO), and anti-thyroglobulin (anti-Tg) antibodies from serum samples were performed by chemiluminescence immunoassay. Maternal serum leptin levels were determined by ELISA. Dried capillary blood spots were used to measure newborn TSH levels. Results: Subjects were divided into two groups according to the neonatal TSH levels using a cut-point of 5.5 mIU/L. Median maternal serum leptin levels were significantly higher in newborns whose TSH levels were higher than >5.5 mIU/L [13.2 µg/L (1.3 – 46.5) vs. 19.7 µg/L (2.4 – 48.5), p<0.05]. Serum leptin levels showed a negative correlation with maternal fT4 (r=0.32, p<0.05), fT3 (r=0.23, p<0.05), and a positive correlation with BMI (r=0.30 p<0.05). Conclusion: Our results suggest that high leptin levels in the third trimester of pregnancy influence maternal thyroid functions and might cause and increase in newborn TSH levels. Detection of high maternal serum leptin levels may be a reason for subclinical hypothyroidism.